1994
DOI: 10.1021/ja00084a033
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Behavior in Metal-Containing Liquid Crystals: A Structure-Activity Study

Abstract: The synthesis and physical characterization (thermotropic and ferroelectric behavior) of eight ortho-palladated dimers [Pd2(ji-C1)2L*2] is reported. They are derived from chiral imines HL* (HL* = />-R1OC6H,(CH=NQH4-OR* 12-p, with R1, R2, or both equal to (R)or (5)-l-methylheptyl). The chiral imines, which contain one or two stereogenic centers, are not liquid crystals themselves. However, the dimeric complexes, which contain two or four stereogenic centers in their structure, exhibit both SmA and SmC* mesophas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Transition metal-complexed azo methine compounds have been studied in great detail in the literature for understanding their optical and electronic properties, structure-redox relationships, mesogenic characteristics [8][9][10][11][12]. Although many Schiff bases and their corresponding metal complexes have been extensively studied, relatively few water-soluble azo-linked Schiff bases and their metal complexes have been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-complexed azo methine compounds have been studied in great detail in the literature for understanding their optical and electronic properties, structure-redox relationships, mesogenic characteristics [8][9][10][11][12]. Although many Schiff bases and their corresponding metal complexes have been extensively studied, relatively few water-soluble azo-linked Schiff bases and their metal complexes have been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the diversity of substituents thus introduced, a great variety of mesogenic complexes has been reported [12]. In this paper we report the preparation of new copper(II) and nickel (II) complexes derived from new bidentate Schiff bases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been well demonstrated that metallomesogens possessing molecular chirality can self-organise to form chiral phases such as the helical structures of the chiral nematic (N*) or chiral smectic C (SmC*) phases (1,2,(10)(11)(12). These features have potential in several applications.…”
Section: Introductionmentioning
confidence: 99%